(untitled) (Nigerian Journal of Technology, 2017)
A multipurpose railroad hand truck comprising mainly of a frame, swinger arm, connecting rod, crank shaft, gears, wheels and brake was designed and fabricated to reduce the cost of material handling in small scaled manufacturing industries. The frame and other major components of the hand truck were fabricated with mild steel bars, shafts and sheets while the guide rail was constructed using 50mm by 50mm mild steel angle bar. The hand truck is hand paddled and requires no prime mover (electric motor, IC engine, etc.), hence incurring minimal operational cost. The hand truck will be used to convey tools, materials and work pieces from one part of the workshop to another on guide rails. Results of its performance test indicated that the hand truck can carry loads up to 250kg. All materials used for the fabrication were sourced locally. http://dx.doi.org/10.4314/njt.v36i2.22